2020
DOI: 10.1155/2020/6626488
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Antimicrobial Susceptibility Profile of Escherichia coli O157 : H7 from Raw Milk of Dairy Cattle in Holeta District, Central Ethiopia

Abstract: A cross-sectional study was conducted in small, medium, and large-scale dairy farms of Holeta district to isolate, identify, and antimicrobial susceptibility profile of Escherichia coli O157 : H7 in raw milk of dairy cattle. A total of 210 lactating cows were selected for raw milk samples, and 19% (40/210) were found to be positive for E. coli whereas 5.2% (11/210) were confirmed as E. coli O157 : H7 positive using the Escherichia coli O157 latex test. Accordingly, all E. coli was highly susceptible to Ciprofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
29
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 31 publications
14
29
6
Order By: Relevance
“…Owing to its important ingredients, it is widely accepted as a full diet. 2,3 In Ethiopia, however, milk consumed annually is poor in comparison with other developing countries' total dairy intake. Local milk production fails to meet the milk requirements of the country because of low inputs and common cattle health conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to its important ingredients, it is widely accepted as a full diet. 2,3 In Ethiopia, however, milk consumed annually is poor in comparison with other developing countries' total dairy intake. Local milk production fails to meet the milk requirements of the country because of low inputs and common cattle health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine mastitis leads to a decrease in milk production, increases culling rate, incurs medical costs, and often leads to severe deaths from infections. 3,6,10 Mastitis is of extreme zoonotic importance since the milk is unsafe for human consumption. This is due to the risk of bacterial contamination of the milk from infected cows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ethiopia, a country which ranks second after Nigeria in the health burden of zoonotic diseases in Africa [28], the epidemiology of food-borne pathogens especially that of pathogenic E. coli is not well studied. However, recently, there is an increasing trend of reporting the occurrence level of the organism in beef, dairy products, and fish [2,3,9,16,[29][30][31][32][33][34][35][36][37]. Besides this, current and detailed studies on the prevalence of antibiotic resistance and multidrug phenotypes of enterohemorrhagic E. coli O157 : H7 in foods of animal origin in different catering establishments are very limited in Ethiopia except for the report of [2,3,9] on beef at butcher shops and restaurants and raw milk and dairy products such as yogurt and cheese derived from raw milk at cafeterias, restaurants, open markets, and supermarkets in Central Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The closest results to this study for the resistant strains of several human isolates were reported by Momtaz et al [ 66 ], who determined that the isolates were more resistant to Oxytetracycline 86%, and Ranjbar et al [ 67 ], Gentamycin, Ciprofloxacin, and aminoglycosides. Higher results for antibiotic resistance were observed by Ababu et al [ 68 ], who noted that the resistance of the isolates for both Oxytetracycline and Gentamycin was 100%. On the other hand, Al-Ajmi et al [ 43 ] stated that 100% of STEC isolates were susceptible to Ciprofloxacin and 84% for Amoxicillin.…”
Section: Discussionmentioning
confidence: 69%